Synthesis and Evaluation of Novel Carboxamides Capable of Causing Centrosome Declustering and Apoptosis in Breast Cancer Cells. Issue 15 (19th April 2022) - Farrukh, Usama B.; Bilal, Aishah; Zahid, Huda; Iqbal, Maheen; Manzoor, Safia; Firdous, Farhat; Furqan, Muhammad; Azeem, Muhammad; Emwas, Abdul‐Hamid; Alazmi, Meshari; Gao, Xin; Saleem, Rahman S. Z.; et al.
Abstract: The fragility of cancer cells at the time of mitosis has served as an important target for the development of many successful chemotherapeutic agents. Many cancers cells have supernumerary centrosomes that they cluster during mitosis to form bipolar spindles. Inhibition of centrosome clustering in these cells results in multipolar spindle formation and apoptotic cell death, providing an opportunity to selectively target a subset of cancers with centrosome amplification. In the current work, we report synthesis of 29 novel tethered biaryls and biological evaluation of their ability to inhibit centrosome clustering in breast cancer cells (BT‐549). We have identified N ‐benzhydryl‐5‐nitrofuran‐2‐carboxamide (5 h) as a centrosome declustering compound. 5 h has potent antiproliferative activity in centrosome amplified BT‐549 cells with GI50 value of 1.81±0.19 μM (n=2). Treatment of BT‐549 cells with 5 h causes centrosome declustering resulting in mitotic arrest due to multipolar spindle formation and misaligned chromosomes which ultimately leads to apoptotic cell death. Abstract : The current work presents synthesis of 29 novel tethered biaryls and their biological evaluation including antiproliferative activity, immunofluorescence and immunoblotting studies. We have identified N ‐benzhydryl‐5‐nitrofuran‐2‐carboxamide (5 h) as a potent centrosome declustering compound with GI50 value of 1.81±0.19 μM (n=2) in centrosome amplified BT‐549 cells. We show that treatment of BT‐549 cells with 5 h causes centrosome declustering resulting in mitotic arrest due to multipolar spindle formation and misaligned chromosomes which ultimately leads to apoptotic cell death.